The internationalization process of the higher education institution: Paraíba State University in focus (Research, Society and Development, 2020)
In the current scenario, marked by globalization, building policies aimed at university internationalization, through cooperation between higher education institutions, are strategic actions that corroborate the university mission. Internationalization of higher education institutions is considered one of the four pillars of higher education, along with teaching, research and extension. From this perspective, this article aims to analyze the confluence between the internationalization process of Paraíba State University - UEPB and the participation of professors in this phenomenon. The methodology used comprises a quantitative and qualitative approach. We used as methodological instrument an online questionnaire, built according to the concepts studied in the theoretical framework, that was made available on the website of that institution from February 28 to March 31, 2019, as well as notes collected in the observation visits made on the eight campuses that make up the university. This research was attended by 107 professors from UEPB. The results showed that the involvement of UEPB professors in the internalization process of the institution is still incipient, thus requiring greater mobilization of the academic community for the effective development of such process, as well as an institutional effort to expand and consolidate international cooperation. Therefore, UEPB needs to invest in institutional policies to strengthen internationalization.